Diversification of Agricultural Production by Implementation of Biomass Action Plan within the EU Energy Policy - Matej POLÁK; Vladimír KOCÁK (Revista de Management Comparat International)
Such as other sectors of industry, the agricultural sector has to find the way how to deal with new conditions within the world financial crisis. Other negatives which this sector has to deal are coming from the grant policy of EU, which creates different conditions in particular member countries. Financial crisis brought to agricultural industry new problems and challenges, which the private farms have to solve by the diversification of their business strategies. Some of the farms have already implemented new steps in their business plans by the growing of biomass for energetic purposes. Authors of the article are assessing the aim and scope of the action plan of biomass exploitation and its transformation to final energy in the farm PD Kapusany. This farm has close cooperation with the University of Economics Bratislava, Technical universities of Kosice and Zvolen. Result of this cooperation is the project of biomass exploitation in energetic sector. There was implemented new biogas station technology with the performance 180 kWh within the project.